Analyzing barriers to the implementation of an eco-toilet system in the Philippines - Ignacio, Jonathan Jared J. (Animo Repository, 2019)
Eco-Toilet System is a waterless technology that plays an important role in water conservation, proper sanitation, and agricultural production. Despite these benefits, the integration and sustained use of an ETS, including in the Philippines, remain a challenge due to barriers that are related to policy, finances, operations, and social acceptance. However, there is a little knowledge about understanding the complex relationships of these barriers and the perceptions of the people concerning the ETS implementation. Thus, an exploratory research was carried out to elucidate the barriers and social perceptions that could hamper the implementation of ETS, particularly in the Philippines. DEMATEL approach was employed to gather experiential data from project developers and policy-makers who had an experience in implementing an ETS. Another approach, which is the integration of the C-TAM-TPB to a PLS-SEM model, was applied to highlight the perception of the target users towards using an ETS. The result of the DEMATEL study showed that the five respondents considered behavioral intention (r + c = 10.694) as the most critical and correlated among the 12 identified barriers in the study. In addition, insufficient awareness raising and user training as well as lack of financial capacity to pay were the most influential barriers with relation scores (r – c) of 2.723 and 2.269, respectively. Meanwhile, the results of C-TAMTPB revealed that the target users of an ETS in a university in Mulanay, Quezon had identified their attitude (β = 0.372; t = 3.609; p < 0.000) and subjective norms (β = 0.539; t = 5.738; p < 0.000) as significant predictors of their behavioral intention towards the use and acceptance of ETS. The adjusted R2 (of BIU = 0.78) and Q2 (> 0) values indicated that the predictive power and relevance of the model was substantial and acceptable. DEMATEL and C-TAM-TPB were able to provide a clearer understanding of the problems underpinning ETS implementation. Decision-makers could consider this information and framework when developing an ETS in the Philippines.